University Mission in Western-European Culture (Ethical and Sociological Aspects) P. ІІ - Sergiy Volodymirovych Kurbatov; Mariya Mikhaylivna Rohozha (Філософія освіти, 2020)
The paper by Sergiy Kurbatov and Mariya Rohozha “The Mission of University in the Western European Culture”(Part II) is devoted to the analyses of transformation of the university as social institution and cultural phenomenon in our time, which we started at the first part of this paper, that was published in “Philosophy of Education”, 2017, № 2 (21)). If the previous paper of these authors included a long chronological period from the origin of the university in late Medieval time up to the 20th century, the current paper is concentrated on analyses of radical challenges, that university faced at the end of the 20th century and at the beginning of the 21st century. For example, such popular in contemporary English language literature concept as the end (or the death) of university is observed. The authors tried to analyze sociological attempts to measure the main university activities in the form of international university rankings and the possibilities to develop in Ukraine the ideal models of university, which any system of university rankings have. The special stress was made on the influence of COVID 19 pandemic on transformative processes and institutional development of universities in the nearest future. The main challenges of the 21st century are crucial for the university, because this institution lost monopoly of producing and distribution of advanced knowledge for the first time in history. From the tactic viewpoint, university is less competitive than the different training programs and online courses, it is too conservative and bureaucratic one. But the authors think that in strategic perspective university has a chance for renovation, proving the old maxima that the values and spiritual dimensions of being and the relevant environment are crucial for human being. Almost the millennium of university history proves its ability to pass through the dramatic historical transformation and to continue to maintain its essence.